(3JLGQH YQHjIs - (3YOfGf MSjf(B, (3jhfSs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2011)
(3GdGWGQ GdeaGgjej ddJehjd GdNGQLj ef GdHdOGf GdfGejI, GdJehjd GdNGQLj ddHdOGf GdfGejI cGMOi BdjGJ GdJUMjM aj GdGbJUGO GdQCSeGdj, GdJehjd GdNGQLj h YdGbJg HSjGSGJ GdGUdGM GdGbJUGOj aj GdHdOGf GdfGejI, GdbQGV GdNGQLjI deUQ h GdGQOf h JhfS aj Xd SjGSGJ GdGUdGM GdGbJUGOj, OhQ GdGSJKeGQGJ GdGLfHjI aj GdJehjd GdNGQLj aj HdOGf GdGUdGM GdYQHjI, BKGQ GdJehjd GdNGQLj h GdGUdGM aj HYV GdeJZjQGJ GdGbJUGOjI h GdGLJeGYjI aj cd ef eUQ, GdGQOf h JhfSs
Keywords: (3GdJNWjW GdEbJUGOjs; (3GdJehjd GdOhdjs; (3GdOjhf GdNGQLjIs